Pelaksanaan Program Layanan Sosial Dan Keterampilan Pada Anak Penyandang Masalah Kesejateraan Sosial (PMKS) Di Panti Sosial - Windy Zulianda; Jalius Jalius (Universitas Negeri Padang, 2022)
This research was motivated by the large number of youth with social welfare problems who managed to have the provisions and abilities through social service programs and skills services held by the Panti Sosial Binan Remaja Harapan Kota Padang Panjang, regardless of their slightly problematic social status.This study uses a qualitative approach, with data sources consisting of research subjects, namely the manager of the Harapan Adolescent Social Institution in the City of Padang Panjang, and research informants, namely students at the Panti Sosial Bina Remaja Harapan City of Padang Panjang. This study uses data collection techniques such as interviews, observations, and documentation, using data reduction, data presentation, and drawing conclusions as data analysis techniques, as well as triangulation of sources and methods for data validity techniques.The results of this study indicate that the implementation of the Social Service and Skills Program for Children with Social Welfare Problems (PMKS) at the Panti Sosial Bina Remaja Harapan City of Padang Panjang, namely: the social service program contains entrepreneurship, social and community relations, ethics and behavior change, religious guidance, women's jurisprudence guidance, psychological guidance, art guidance, sports and others. Meanwhile, the skills service program includes sewing and embroidery skills. Overall, the implementation in the field went smoothly, and was in accordance with the expectations of the Padang Panjang City Community Development Center for Youth Hope. The results of the program are also in accordance with what has become the target of the program itself, such as students who have the courage to socialize with local residents by showing good ethics, have been able to produce clothes for everyday use, and some have started to open businesses. sew yourself and even sell the stitches